Students’ Response to the Basic Physics Textbook Integrated with Faith, Piety, and Local Wisdom - Lutfiyanti Fitriah (Jurnal Ilmiah Pendidikan Fisika, 2020)
This research was conducted due to the unavailability of textbook in lecture of Basic Physics 1. The aim of this research was to describe the response of students to basic physics textbook that contained the value of faith and piety and integrated with South Borneo local wisdom in the direct instruction model setting that has been developed. The method of this research was descriptive analytic. The subjects of the try out were 17 first-semester students of the Physics Education Department Faculty of Education and Teacher Training UIN Antasari Banjarmasin who participated in the Basic Physics 1 lecture in the 2018/2019 academic year. Data was obtained through student response questionnaires. Data were analyzed quantitatively and qualitatively. The results showed that students' response to the content, appearance, and language of textbook were in the good criteria with an average score of 4.31 and 100% of students stated that they were interested in using the textbook. It could be concluded that the basic physics textbook integrated with faith, piety, and local wisdom in direct instruction model setting is feasible to use in the Basic Physics 1 lecture.